2018
DOI: 10.1161/jaha.117.007155
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Coronary Artery Calcium Score: Cross‐Sectional Results of ELSA‐Brasil (Brazilian Longitudinal Study of Adult Health)

Abstract: BackgroundAvailable evidence for the relationship between coffee intake and subclinical atherosclerosis is limited and inconsistent. This study aimed to evaluate the association between coffee consumption and coronary artery calcium (CAC) in ELSA‐Brasil (Brazilian Longitudinal Study of Adult Health).Methods and ResultsThis cross‐sectional study is based on baseline data from participants of the ELSA‐Brasil cohort. Only participants living in São Paulo, Brazil, who underwent a CAC measurement (n=4426) were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The benefits and risks of coffee intake have been the subjects of contentious debate for decades. The existing evidence on coffee intake and subclinical atherosclerosis is inconsistent [3538, 56, 57]. We found an inverted J-shaped association between coffee intake and CCA-IMT, with the largest CCA-IMT observed among occasional drinkers with less than 2 cups of daily coffee intake.…”
Section: Discussionmentioning
confidence: 54%
“…The benefits and risks of coffee intake have been the subjects of contentious debate for decades. The existing evidence on coffee intake and subclinical atherosclerosis is inconsistent [3538, 56, 57]. We found an inverted J-shaped association between coffee intake and CCA-IMT, with the largest CCA-IMT observed among occasional drinkers with less than 2 cups of daily coffee intake.…”
Section: Discussionmentioning
confidence: 54%
“…While drip filter coffee is the most popular brewing method worldwide, plunger coffee dominates in northern Europe. Turkish coffee is popular in the Middle East, Greece, Turkey, and Eastern Europe, and Espresso and Moka methods are the most common in Italy, Spain, and Portugal [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Tea habits also vary around the world [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some studies have investigated the association between CAC and specific beverages (i.e. coffee and sugar-sweetened beverages) (10,11) and a review reported evidence for micronutrients (12) , few studies (13,14) have evaluated the relationship between dietary patterns and CAC. Dietary pattern analysis, which reflects the complexity of dietary intake, accounts for cumulative and interactive effects and reflects actual eating habits and might be useful in the context of prevention of CVD (15,16) .…”
mentioning
confidence: 99%